2019
DOI: 10.1002/cpt.1609
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Mucosal Healing in Inflammatory Bowel Diseases: Which Drug Concentrations Need to Be Targeted?

Abstract: Biologicals introduced a major shift in the treatment of patients suffering from inflammatory bowel diseases. Despite providing a tight disease control for many patients, a considerable proportion of patients will fail to respond favorably to treatment or will lose response over time. Therapeutic drug monitoring emerged as a valuable tool to guide clinical decision making as serum drug concentrations have been linked to outcomes. Focusing on mucosal healing as the ultimate treatment goal, different drug concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…3 The treatment regimens for most of the approved biologics for IBD include an initial short-term, high-dose (or more frequently dosed) induction period followed by a long-term, low-dose maintenance period. 38 Infliximab is the first therapeutic protein approved for IBD treatment. For both CD and UC, the dosing regimen for infliximab is 5 mg/kg IV administration at Weeks 0, 2, and 6 (i.e., induction), then followed by 5 mg/kg every 8 weeks (i.e., maintenance).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The treatment regimens for most of the approved biologics for IBD include an initial short-term, high-dose (or more frequently dosed) induction period followed by a long-term, low-dose maintenance period. 38 Infliximab is the first therapeutic protein approved for IBD treatment. For both CD and UC, the dosing regimen for infliximab is 5 mg/kg IV administration at Weeks 0, 2, and 6 (i.e., induction), then followed by 5 mg/kg every 8 weeks (i.e., maintenance).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated mucosal healing in patients with IBD treated with biological agents such as anti-TNF, anti-integrin, and anti‐interleukin agents, and mucosal healing has been associated with reduced inflammation. 38 , 39 Reduction in inflammation and mucosal healing are expected to result in less macromolecule distribution. Indeed, the reflection coefficient for colon in IBD mice was estimated to be significantly lower than that in the non-IBD mice (0.391 vs. 0.978), providing evidence that CNTO 5048 distribution to the IBD colon would be substantially lower when the inflammation is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Use of biologics in the treatment of inflammatory bowel disease is an emerging example. Van den Berghe et al 6 describe the advances in this field. They review the current evidence that supports the use of TDM in inflammatory bowel disease, showing that mucosal healing can be improved by acting upon serum concentrations of therapeutic antibodies against TNF, integrin, and interleukin-12/23.…”
Section: Precision Medicine In Clinical Pharmacologymentioning
confidence: 99%
“…Existing clinical applications have confirmed that conventional drugs such as aminosalicylates, corticosteroids, and immunosuppressants were indeed effective in reducing colonic inflammation and achieving a certain duration of remission, but their effects in promoting intestinal mucosa healing was limited [10] . The unhealed mucosa facilitates the recurrent invasion of pathogenic factors, subsequently inducing IBD relapse [6,9,11–13] . In recent years, a large number of clinical studies have shown that mucosal healing and barrier function recovery are key endpoints of UC treatment, which can not only help reduce inflammation, promote epithelial repair, relieve clinical symptoms and prevent disease progression, but can also help avoid long‐term clinical need for steroids and reduce hospitalization and surgical excision rates [12,14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…[10] The unhealed mucosa facilitates the recurrent invasion of pathogenic factors, subsequently inducing IBD relapse. [6,9,[11][12][13] In recent years, a large number of clinical studies have shown that mucosal healing and barrier function recovery are key endpoints of UC treatment, which can not only help reduce inflammation, promote epithelial repair, relieve clinical symptoms and prevent disease progression, but can also help avoid long-term clinical need for steroids and reduce hospitalization and surgical excision rates. [12,14,15] Therefore, promoting mucosal barrier repair is also an important approach for the treatment of UC.…”
Section: Introductionmentioning
confidence: 99%